2022
DOI: 10.29390/cjrt-2022-029
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity and burnout among respiratory therapists in Jeddah City, Saudi Arabia

Abstract: Background/objective Burnout is a condition in which a person feels physically fatigued and mentally drained. It occurs after a long period of work-related stress and may lead to mental disorders, such as depression and anxiety. Therefore, healthcare providers especially require early intervention. Regular physical activity has been reported to benefit individuals with mental illness, suggesting that a relationship between physical activity and burnout might exist. Hence, this study’s objective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The included studies reported a total of 3610 responding individuals, with nine studies presenting the demographic characteristics of their respondent population ( n = 2100, 58%) [ 20 , 22–24 , 26 , 29–31 , 33 ]. The reported mean or median ages ranged from 20 to 40 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies reported a total of 3610 responding individuals, with nine studies presenting the demographic characteristics of their respondent population ( n = 2100, 58%) [ 20 , 22–24 , 26 , 29–31 , 33 ]. The reported mean or median ages ranged from 20 to 40 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported the risk factors of burnout [ 20 , 23–26 , 30 , 31 , 33 ]. Female pulmonologists or respiratory therapists tended to experience more burnout than their male counterparts [ 20 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation